Modelo de avaliação do nível de maturidade das tecnologias da indústria 4.0 aplicado ao setor sucroenergético - Marinho, Clésio Aparecido (2020)
The intensification of digital technologies in the industrial environment may require new management practices in the context of the Fourth Industrial Revolution, also known as Industry 4.0. It is believed that such technologies are capable of increasing the competitiveness of companies, as well as facilitating human/machine interaction and integration between customers and suppliers in the production chain. This dissertation aims to evaluate how the industrial processes of the energy sector are implementing the technologies and concepts of Industry 4.0, considering the technological, managerial and strategic bottlenecks. For this, a literature review was conducted, from which it was possible to identify seven models of maturity for Industry 4.0. The in-depth analysis of these publications resulted in the construction of a maturity model directed to the sugar-energy sector. The proposed model contains five dimensions: Strategy, Data Management, Work Teams, Vertical Integration and Horizontal Integration. The operationalization of this maturity model is based on the structure of the National Quality Award. To empirically test this model, a case study was conducted in two companies in the sugar-energy sector. This study captured the interviewees' perception of the implementation of the concepts and technologies of Industry 4.0 in industrial processes. The results revealed that the companies participating in the research are already applying the concepts of industry 4.0 in the management of their industrial processes, so that the evaluated companies obtained 731 and 788 points out of 1000 possible, and that the proposed maturity model can help the development of digital transformation strategies in organizations in the sugar-energy sector.